Hänsel e Gretel: fiaba per adulti e genitori - Paolo Levrero (Firenze University Press, 2019)
Taking back to the cultural context of the German Neuhumanismus the work realized by the brothers Jacob and Wilhelm Grimm in the search and arrangement of fairy tales coming from the tradition of Germanic popular poetry, the article focuses in particular on the fairy tale Hänsel und Gretel, considering its narrative structure and the pedagogical meanings enclosed, aimed at both the world of children and adults.